2018
DOI: 10.3892/mmr.2018.9330
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of miR‑935 increases paclitaxel sensitivity via regulation of SOX7 in non‑small‑cell lung cancer

Abstract: Sex determining region Y‑box (SOX)7 is a member of the SOX family and is responsible for various developmental processes. As a tumor suppressor, decreased expression of SOX7 has been observed in several cancer types, including non‑small‑cell lung cancer (NSCLC). However, the mechanism underlying SOX7 downregulation and its role in chemoresistance in NSCLC remains poorly understood. In the present study, the inhibition of microRNA (miR)‑935 increased the expression of SOX7 at the mRNA and protein levels in A549… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Conversely, miR-935 is reported as an onco-miR in gastric cancer that inhibits SOX7 (55), in non-small cell lung cancer that inhibits IL-27 (41), in non-small-cell lung cancer that inhibits SOX7 (56), in hepatocellular carcinoma that inhibits SOX7 and activates c-Myc and cyclin D1 (57), in pancreatic carcinoma that inhibits INPP4A and possibly p27 (58), and in colorectal cancer that targets INPP4A (59). In addition, overexpression of miR-935 has been reported in stathmindepleted neuroblastoma (60), Helicobacter pylori-positive gastric cancer (using Gene Expression Omnibus database) (61), stage-I endometrioid endometrial cancer (62), bladder cancer (63), and chronic hepatitis B that progressed to cirrhosis/hepatocellular carcinoma (64).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, miR-935 is reported as an onco-miR in gastric cancer that inhibits SOX7 (55), in non-small cell lung cancer that inhibits IL-27 (41), in non-small-cell lung cancer that inhibits SOX7 (56), in hepatocellular carcinoma that inhibits SOX7 and activates c-Myc and cyclin D1 (57), in pancreatic carcinoma that inhibits INPP4A and possibly p27 (58), and in colorectal cancer that targets INPP4A (59). In addition, overexpression of miR-935 has been reported in stathmindepleted neuroblastoma (60), Helicobacter pylori-positive gastric cancer (using Gene Expression Omnibus database) (61), stage-I endometrioid endometrial cancer (62), bladder cancer (63), and chronic hepatitis B that progressed to cirrhosis/hepatocellular carcinoma (64).…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanisms underlying Taxol resistance have not yet been fully elucidated, emerging evidence has shown that miRNAs and lncRNAs play a critical role in the Taxol resistance of NSCLC 29,30 . The roles of circRNAs in the Taxol resistance of NSCLC have barely been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Another miRNA molecule proved to have binding properties to the 3'UTR region of the SOX7 transcript is miR-935. miR-935 has already been reported to downregulate SOX7 expression in liver, gastric and lung cancers [86,105,106]. Downregulation of SOX7 via miR-935 promotes cell invasion and cell proliferation, as well as cell apoptosis in all the aforementioned types of cancer.…”
Section: Sox7mentioning
confidence: 95%
“…It has been observed that miR-935 was clearly upregulated in NSCLC tissues compared to non-malignant lung tissue. Knockdown of miR-935 resulting in an increased SOX7 expression leads to the promotion of cell proliferation arrest and cell apoptosis of the lung cancer adenocarcinoma cell line A549 [105]. This could be due to the reduction in the expression level of the Bcl-2 protein and the activity of p-Akt, resulting in an increase in the expression of the proapoptotic Bax protein.…”
Section: Sox7mentioning
confidence: 99%